Immunity and host defence mechanism in patients undergoing CAPD - Naganuma, Shinji; Hayasaka, Yutaro; Teraoka, S.; Ota, Kazuo (Journal of Japanese Society for Dialysis Therapy, 1988)
Peritonitis is one of the most serious complications, leading to the discontinuation of CAPD. In the present study, we examined several social factors and immunological parameters in CRF patients undergoing CAPD or HD. The patients were divided into three groups: group 1, patients having no episode of peritonitis, group 2, patients with a high incidence of peritonitis, and group 3, hemodialysis patients. With regard to systemic immunological status, the serum levels of IgG, IgM, IgA, C3, C4, peripheral lymphocyte counts and their subsets (two-parameter analysis), lymphocyte stimulation by PHA and ConA, and interleukin-2 production were measured. The levels of IgG, IgM, IgA, C3 and C4 in the effluent were also determined at the same time. If was found that the natural killer cell activity of lymphocyte subsets and interleukin-2 production were significantly higher in group 1 than in group 2. Several social factors associated with peritonitis differed between groups 1 and 2. Soluble suppressor factor in CAPD patients had immunosuppessive activity in the MLC reaction. For other parameters, no significant differences were observed between groups 1 and 2. From these results, the occurrence of peritonitis was considered to be related to immunological deficiency in the host, presumably caused by suppressed cellular immunity and local defence mechanism.